2008
DOI: 10.1111/j.1365-2818.2008.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

On the orientations of abnormally grown grains in nanocrystalline Ni and Ni–Fe

Abstract: The scanning electron microscopy-based electron backscatter diffraction technique has been used to determine grain orientations of abnormally grown grains upon annealing in nanocrystalline Ni and Ni-20 at.% Fe electrodeposits. The results show that in nanocrystalline Ni and Ni-Fe, the first grown grains that can be detected are 411 oriented with respect to the normal direction (411//ND). Upon annealing, further grain growth occurs and the dominant orientation of the abnormally growing grains changes from 411//… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…7 as an example of the distribution of twin boundaries in the material. Klement et al reported in similar studies on texture evolution in nanocrystalline Ni the development of a 1 1 4 //ND texture in the early stages of grain growth [11]. This difference in texture development may be due to a number of factors, including differences in sample composition (due to different sample synthesis methods), initial grain size, thickness, or annealing temperature.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…7 as an example of the distribution of twin boundaries in the material. Klement et al reported in similar studies on texture evolution in nanocrystalline Ni the development of a 1 1 4 //ND texture in the early stages of grain growth [11]. This difference in texture development may be due to a number of factors, including differences in sample composition (due to different sample synthesis methods), initial grain size, thickness, or annealing temperature.…”
Section: Resultsmentioning
confidence: 95%
“…Past in situ TEM experiments that focused on growth front velocities have suggested that this start/stop growth results from the accumulation of impurity elements at the grain boundaries [9]. Experiments on the texture development in annealed electrodeposited nanocrystalline Ni revealed the development of a 1 1 1 //ND texture via a twinning mechanism [10] with some studies also reporting an initial 1 1 4 //ND texture [11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous results show that twinning is kinetically favoured over the growth of (111) oriented grains. 41 However, the role of twinning is not yet clear. Our quantitative XRD results on the planar fault probabilities of various samples are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to literature [5][6][7], the addition of saccharin leads to the formation of fine crystallites that have a preferred <111> orientation with the growth direction (GD). But also double fibre textures have been observed in Ni and Ni-base alloys in the presence of additives: a <200> <111> double fibre texture was found for Ni with 10 and 20 nm grain size and a sulphur content of 1580 ppm and 1200 ppm, respectively [8], and a <411> <111> double fibre texture was observed in Ni and Ni-Fe electrodeposits by using X-ray diffraction and by performing measurements using electron backscatter diffraction (EBSD) technique [9]. Upon annealing, abnormal and normal grain growth sets in and the final <111> texture with respect to GD is obtained with one or two twinning operations from the initial texture of the as prepared material [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%